Hemotherapy support in HSCT - De Lima Prata, Karen; Tieme Kondo, Andrea; Miranda de Souza, Aline; Marcele da Costa Lira, Sanny; Alice Feitosa Ribeiro, Andreza (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
Hemotherapy support is essential for Hematopoietic Stem Cell Transplantation (HSCT). In this article, we highlight the main points published in the 2020 SBTMO consensus and provide a brief update on the topic.